Gastos públicos no Brasil s\~ao produtivos? - José Oswaldo Cândido Júnior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2001)
– The worry with the effects of public expenditures is appeal, mainly for their impacts on economic growth. Many papers suggest that public expenditures should raise the private productivity and the economic growth. On the one hand, an expansion of public expenditures that are financed by distortionary taxes and the inefficiency on the allocation of resources could overcome the positive effects of externalities. This paper analyses the aggregate relation between public expenditures and economic growth in Brazil from 1947 to 1995. The relation tries to catch the net balance of participation of expenditures on GDP. The value of elasticity expenditure-GDP and the differential of productivity public-private are negatives. The results suggest that the proportion of government spending in Brazil is above of optimal level and there is indication of low productivity. The effects on economic growth are more harmful as more distortionary is tax system.
Keywords: 330; Öffentliche Ausgaben; Wirtschaftswachstum; Brasilien